An intensity study of the torsional bands of ethane at 35 µm. (January 2015) - Moazzen-Ahmadi, N.; Norooz Oliaee, J.; Ozier, I.; Wishnow, E.H.; Sung, K.; Crawford, T.J.; Brown, L.R.; Devi, V.M.
Abstract: Ethane is the second most abundant hydrocarbon detected in the outer planets. Although the torsional mode is not infrared active in the lowest order, the strongest feature in this band can be seen near 289 cm −1 in the CASSINI CIRS spectrum of Titan. Prior laboratory studies have characterized the torsional frequencies to high accuracy and measured the intensities to temperatures as low as 208 K. However, for the interpretation of the far-infrared observations of Titan, further investigation was needed to determine the intensities at lower temperatures and to higher accuracy. The spectrum of C2 H6 was investigated from 220 to 330 cm −1 to obtain the band strengths of the torsional fundamental ν 4 (near 289 cm −1 ) and the first torsional hot band ( 2 ν 4 − ν 4 ). Seven laboratory spectra were obtained at resolutions of 0.01 and 0.02 cm −1 using a Bruker IFS-125 Fourier transform spectrometer at the Jet Propulsion Laboratory. The interferometer was coupled to a coolable multi-pass absorption cell set to an optical path length of 52 m. The range of temperatures was 166–292 K with the lower temperatures being most relevant to the stratosphere of Titan. The ethane sample pressures ranged from 35 to 254 Torr. The modeling of the transition intensities required the expansion of the dipole moment operator to higher order; this introduced Herman-Wallis like terms. The fitting process involved five independent dipole constants and a single self-broadening parameter. The results presented should lead to an improved understanding of the methane cycle in planetary atmospheres and permit other molecular features in the CIRS spectra to be identified. Highlights: Seven C2 H6 FTIR spectra recorded at temperatures from 166 to 292 K were studied. The dipole moment operator has been expanded to include the Herman-Wallis type terms. For the lowest temperature spectra, the residuals in intensities are less than 1%. Band strengths of the torsional mode ν 4 and the hot band 2 ν 4 − ν 4 were obtained. This research can be applied to the interpretation of CIRS FIR spectra of Titan.